A Facile Preparation of Titanium Dioxide-Iron Oxide@Silicon Dioxide Incorporated Reduced Graphene Oxide Nanohybrid for Electrooxidation of Methanol in Alkaline Medium - Yusoff, N.; Kumar, S.V.; Rameshkumar, P.; Pandikumar, A.; Shahid, M.M.; Rahman, M.A.; Huang, N.M. (Elsevier, 2016)
An iron oxide-silicon dioxide coated titanium dioxide (TiO2-Fe2O3@SiO2) incorporated reduced graphene oxide (rGO) nanohybrid was prepared by a simple hydrothermal method using titanium tetraisopropoxide (TTIP) and graphite flakes as the precursors. Tetraethoxysilane (TEOS) was used to form a SiO2 coating on Fe2O3 nanoparticle surface (Fe2O3@SiO2). The presence of SiO2 layer would facilitate the formation of Fe2O3 on the TiO2 surface by an electrostatic attraction that led to the formation of TiO2-Fe2O3@SiO2. The transmission electron microscopy (TEM) results revealed the successful attachment of Fe2O3@SiO2 particles to the TiO2 surface and a uniform distribution of TiO2-Fe2O3@SiO2 composites on the rGO sheet. Furthermore, the rGO/TiO2-Fe2O3@SiO2 nanohybrid modified platinum (Pt) electrode was used for the electrocatalytic oxidation of methanol in alkaline medium. The rGO/TiO2-Fe2O3@SiO2 nanohybrid with weight ratio of 1:3:1 (rGO:TiO2:Fe2O3) showed a higher electrocatalytic activity toward methanol oxidation with an anodic peak current density of 2.45 mA/cm2. Moreover, the nanohybrid displayed a higher stability with 91.58% retention of the initial current density after 5000 s in long term current-time curve. This newly prepared rGO/TiO2-Fe2O3@SiO2 nanohybrid could be a promising anodic catalyst for the direct methanol fuel cells (DMFCs) application.